2021
DOI: 10.1002/jsfa.11506
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Flavourzyme on flavor, antioxidant activity, and sensory attributes of salted grass carp by brine injection and brining

Abstract: Background: Enzyme injection is vital for improving the sensory attributes and processing characteristics of meat products by enhancing proteolysis. However, studies regarding the appropriate dose addition for accelerating protein degradation in grass carp are minimal. This study aimed to investigate the impact of Flavourzyme® on the flavor quality and antioxidant activity of salted grass carp via brine injection and brining.Results: Flavourzyme was added at doses of 0, 5, 10, 20, and 30 leucine aminopeptidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Therefore, it is necessary to explore a method to enhance the flavor of shucked oysters and investigate the quality degradation mechanism during storage. Currently, many studies have confirmed that the addition of exogenous proteases could improve the flavor quality of aquatic products in a short time by promoting the generation of flavor amino acids and flavor nucleotides [4,5]. While most of the present studies have focused on exploring the production of umami peptides from homogenized oysters using hydrolytic enzyme treatment [6,7], this method may not align with typical consumption habits.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, it is necessary to explore a method to enhance the flavor of shucked oysters and investigate the quality degradation mechanism during storage. Currently, many studies have confirmed that the addition of exogenous proteases could improve the flavor quality of aquatic products in a short time by promoting the generation of flavor amino acids and flavor nucleotides [4,5]. While most of the present studies have focused on exploring the production of umami peptides from homogenized oysters using hydrolytic enzyme treatment [6,7], this method may not align with typical consumption habits.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, hydrolysis was extensively applied in the preparation of the degradation products of fish proteins to improve the flavor and the quality of the food. Wu et al 6 improved the sensory attributes of salted grass carp using brine injection through an appropriate Flavourzyme hydrolysis process. Ruan et al 7 added enzymatic hydrolysate of low-value fish to soy sauce in the fermentation process, which improved the flavor and quality of traditional soy sauce.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hydrolysis was extensively applied in the preparation of the degradation products of fish proteins to improve the flavor and the quality of the food. Wu et al 6 . improved the sensory attributes of salted grass carp using brine injection through an appropriate Flavourzyme hydrolysis process.…”
Section: Introductionmentioning
confidence: 99%